Effect of stocking density on growth, survival and feed utilization of Labeo rohita reared in cage in a tropical reservoir - Swain, H. S.; Upadhyay, A.; Ramteke, M. H.; Meena, D. K.; Sarkar, U. K.; Sahoo, A. K.; Chadha, N. K.; Rawat, K. D.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2022)
Labeo rohita (30.35Â±1.08 g) was reared in cages for 240 days at three stocking densities, viz., 10 nos.m-3 (R10), 20 nos.m-3 (R20), and 30 nos.m-3 (R30) in triplicates at Salia reservoir, Odisha, India. The fishes were fed with commercial floating pellet feed (CP: 28%, CL: 4%) @ 5-3% of the body weight. L. rohita stocked @10 nos. m-3 showed a significantly higher (P0.05) between R10 and R20, however, survival (%) was different at different stocking densities (P